(E)-Nerolidol is a volatile signal that induces defenses against insects and pathogens in tea plants. (1st April 2020) - Chen, Shenglong; Zhang, Liping; Cai, Xiaoming; Li, Xin; Bian, Lei; Luo, Zongxiu; Li, Zhaoqun; Chen, Zongmao; Xin, Zhaojun
Abstract: Plants release large amounts of volatile organic compounds (VOCs) in response to attackers. Several VOCs can serve as volatile signals to elicit defense responses in undamaged tissues and neighboring plants, but many questions about the ecological functions of VOCs remain unanswered. Tea plants are impacted by two harmful invaders, the piercing herbivore Empoasca ( Matsumurasca ) onukii Matsuda and the pathogen Colletotrichum fructicola . To determine the VOC signals in tea, we confirmed CsOPR3 as a marker gene and set up a rapid screening method based on a 1.51 kb CsOPR3 promoter fused with a β-glucuronidase (GUS) reporter construct ( OPR3p::GUS ) in Arabidopsis . Using this screening system, a terpenoid volatile ( E )-nerolidol was identified as a potent signal that elicits plant defenses. The early responses triggered by ( E )-nerolidol included the activation of a mitogen-activated protein kinase and WRKY, an H2 O2 burst, and the induction of jasmonic acid and abscisic acid signaling. The induced plants accumulated high levels of defense-related chemicals, which possessed broad-spectrum anti-herbivore or anti-pathogen properties, and ultimately triggered resistance against Empoasca onukii and Colletotrichum fructicola in tea. We propose that these findings can supply an environmentally friendly management strategy for controlling an insect pest and a disease of tea plants.